2018
DOI: 10.1111/jicd.12366
|View full text |Cite
|
Sign up to set email alerts
|

Are coronectomy studies being cited? A bibliometric study

Abstract: Aim The aim of the present bibliometric study was to analyze the citations received by coronectomy papers and their references. Methods Data were extracted from the Web of Science online database. After excluding irrelevant papers, full record and cited references from 79 papers were downloaded and imported into VOSviewer and CRExplorer for bibliometric analyses. Results The 79 papers on coronectomy collectively had 9.7 citations per paper. The h‐index of this collection of papers was 17. The top five major co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Liu et al 20 conducted a bibliometric analysis of recent trends and characteristics of oral potentially malignant disorders (OPMD). Yeung, Wong, & Leung 21 analysed the citation received by coronectomy papers and found that the papers dealing with postoperative morbidity had high citation counts. Gondivkar et.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 20 conducted a bibliometric analysis of recent trends and characteristics of oral potentially malignant disorders (OPMD). Yeung, Wong, & Leung 21 analysed the citation received by coronectomy papers and found that the papers dealing with postoperative morbidity had high citation counts. Gondivkar et.…”
Section: Introductionmentioning
confidence: 99%
“…The extracted data was also imported into CRExplorer (v.1.9, 2018), a computer program that performs cited reference analysis (Thor et al, 2016), and outputs the results as a “reference publication year spectroscopy” (RPYS) that shows a waveform with high peaks in years when the seminal references were published (Slotkin, 1999; Marx et al, 2014; Yeung and Wong, 2019; Yeung et al, 2019c). For instance, the articles published in years 1926, 1927, 1928, 1929, and 1930 were cited by the publications within the dataset 45, 52, 146, 56, and 55 times, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we have performed a cited reference analysis using the CRExplorer software (Thor et al, 2016). It can plot a “reference publication year spectroscopy” (RPYS), which shows a waveform along the timeline, and the waveform illustrates in which years the more cited references (compared to preceding and succeeding years) were published (Marx and Bornmann, 2014; Marx et al, 2014; Wray and Bornmann, 2015; Yeung, 2017; Yeung et al, 2019). The primary aims of the current study were to identify the historical root of VAS by RPYS and confirm if it was Hayes and Patterson (1921).…”
Section: Introductionmentioning
confidence: 99%